2010
DOI: 10.1155/2010/415148
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Fluxes, Reaction Replaceability, and Response to Enzymopathies in the Human Red Blood Cell

Abstract: Characterizing the capabilities, key dependencies, and response to perturbations of genome-scale metabolic networks is a basic problem with important applications. A key question concerns the identification of the potentially most harmful reaction knockouts. The integration of combinatorial methods with sampling techniques to explore the space of viable flux states may provide crucial insights on this issue. We assess the replaceability of every metabolic conversion in the human red blood cell by enumerating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(29 citation statements)
references
References 34 publications
2
27
0
Order By: Relevance
“…This definition of essentiality is identical to the one used in early work on constraint-based models 26 as well as more recently in ref. 27 , but differs from non-standard topological approaches 6 and the flux surplus rather than flux balance model 28 .…”
Section: Resultsmentioning
confidence: 99%
“…This definition of essentiality is identical to the one used in early work on constraint-based models 26 as well as more recently in ref. 27 , but differs from non-standard topological approaches 6 and the flux surplus rather than flux balance model 28 .…”
Section: Resultsmentioning
confidence: 99%
“…• according to [20], the net flux of all reactions is in the forward direction, except R5PI (which is found to be operating bidirectionally), and PGI and ApK (which are found to have a net backward flux).…”
Section: Exploring the Gibbs Energy Landscape Of The Hrbc Metabolic Nmentioning
confidence: 95%
“…As applications, we focus on two metabolic networks of rather different complexity. First, we shall obtain a detailed reconstruction of the Gibbs energy landscape underlying metabolic activity in the human red blood cell (hRBC) starting from the flux maps obtained in [19] , [20] . Then, the metabolic network of Escherichia coli , iAF1260 [21] , will be analyzed to eliminate infeasible cycles from randomly generated flux configurations.…”
Section: Introductionmentioning
confidence: 99%
“…Work performed along these lines for the bacterium Escherichia coli [40,41] has shown that environment selection restricts the feasible states according to (42) to flux configurations that both reproduce well the available empirical evidence on E.coli's metabolic fluxes and guarantee that the correct physiological task (in that case, growth or biomass production) is carried out by the cell without the need of additional ad hoc functional constraints. We want to add here further evidence supporting the relevance of Von Neumann's observations in the context of cell metabolism.…”
Section: Application To Cellular Metabolismmentioning
confidence: 99%
“…dissimilar) the two configurations are. Likewise, we define the overlap between the vectors c that correspond to the production profiles in each solution of (42). The distributions of these overlaps are displayed in Figure 5.…”
Section: Application To Cellular Metabolismmentioning
confidence: 99%